The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/f8120497
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Recovery of Hemlock Woolly Adelgid (Adelges tsugae) in Response to Winter Temperatures and Predictions for the Future

Abstract: Eastern (Tsuga canadensis) and Carolina hemlocks (T. caroliniana) of eastern North America have been attacked by the non-native hemlock woolly adelgid (Adelges tsugae Annand) (HWA) since the first half of the 20th century. Unlike most insects, HWA develops through one generation from fall to late winter, exposing this insect to the lethal effects of winter temperatures. The mortality inflicted by winter temperatures on HWA determines the surviving population density as well as its ability to spread to uninfest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 53 publications
1
32
0
Order By: Relevance
“…With the lag effect in HWA and predator numbers as they relate to tree health [18], additional years of monitoring are needed to capture the lag effects we suspect are at work. Extreme cold temperatures associated with the polar vortex reduced HWA densities at our study sites [27], which gave trees an opportunity to rebound from pest attack.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…With the lag effect in HWA and predator numbers as they relate to tree health [18], additional years of monitoring are needed to capture the lag effects we suspect are at work. Extreme cold temperatures associated with the polar vortex reduced HWA densities at our study sites [27], which gave trees an opportunity to rebound from pest attack.…”
Section: Discussionmentioning
confidence: 84%
“…We found a 29% increase in odds of finding beetles with each increase in plant hardiness zone (i.e., 5b to 6a), suggesting that warmer plant hardiness zones are more suitable for Laricobius spp. Sites in the warmer hardiness zones did not get the same extreme winter temperatures during the polar vortex [27], which led to a smaller decline in HWA density and in Laricobius spp. populations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the HWA MaxEnt model, mean January and February precipitation were observed as important predictors. In previous HWA studies, minimum winter temperatures have been identified as a major limiting factor for HWA distribution (Paradis et al 2008;McAvoy et al 2017;Tobin et al 2017). However, only the mean minimum October temperature was found among the used 27 climatic variables in the final models and it was not an important predictor.…”
Section: Feature Selection For the Maxent Niche Modelsmentioning
confidence: 88%
“…The high susceptibility of the host species combined with lack of natural enemies, rapid reproduction, and several vectors have provided for the successful performance and fast spreading of HWA in the eastern USA (McClure 1987;McClure and Cheah 1999;Trotter and Shields 2009). The species was recorded for the first time in the eastern USA in Richmond of Virginia, in 1951 (Stoetzel 2002), although the introduction has most likely been much earlier (McAvoy et al 2017). In the beginning, HWA spread slowly in ornamental settings and was not considered as a pest.…”
Section: Hemlock Woolly Adelgid (Hwa) (Iii IV Vi)mentioning
confidence: 99%